Phenytoin potentiates interleukin-1-induced prostaglandin biosynthesis in human gingival fibroblasts. - Modéer, T. (1992)
1. The effect of phenytoin (PHT) on prostaglandin E2 (PGE2) biosynthesis in human gingival fibroblasts stimulated by interleukin-1 (IL-1 alpha, IL-1 beta) or by tumour necrosis factor alpha (TNF alpha) was studied. 2. IL-1 alpha (1.5-6.0 ng ml-1) and IL-1 beta (30-300 pg ml-1), dose-dependently, stimulated PGE2 formation, in 24 h cultures, with IL-beta being the most potent agonist. 3. PHT (2.5-20 micrograms ml-1) did not induce PGE2 formation itself but potentiated IL-1 alpha- and IL-1 beta-induced PGE2 formation in the gingival fibroblasts in a manner dependent on the concentrations of both IL-1 and PHT. 4. IL-1 beta (0.1-1.0 ng ml-1) induced release of [3H]-arachidonic acid ([3H]-AA) from prelabelled fibroblasts that was potentiated by PHT (20 micrograms ml-1). 5. TNF-alpha (greater than or equal to 0.01 micrograms ml-1) significantly stimulated the biosynthesis of PGE2 by a process that was potentiated by PHT. 6. Addition of exogenous arachidonic acid (AA) (greater than or equal to 1 microM) caused an increase of PGE2 formation in the fibroblasts that was not potentiated by PHT (20 micrograms ml-1). 7. The results indicate that treatment with PHT results in upregulation of prostaglandin biosynthesis in gingival fibroblasts challenged with IL-1 or TNF alpha, at least partly due to enhanced level of phospholipase A2 activity.